A mitochondria-targeted caffeic acid derivative reverts cellular and mitochondrial defects in human skin fibroblasts from male sporadic Parkinson's disease patients - Deus, Cláudia M. (2021)
Parkinson's Disease (PD) is a neurodegenerative disorder affecting more than 10 million people worldwide. Currently, PD has no cure and no early diagnostics methods exist. Mitochondrial dysfunction is presented in the early stages of PD, and it is considered an important pathophysiology component. We have previously developed mitochondria-targeted hydroxycinnamic acid derivatives, presenting antioxidant and iron-chelating properties, and preventing oxidative stress in several biological models of disease. We have also demonstrated that skin fibroblasts from male sporadic PD patients (sPD) presented cellular and mitochondrial alterations, including increased oxidative stress, hyperpolarized and elongated mitochondria and decreased respiration and ATP levels. We also showed that forcing mitochondrial oxidative phosphorylation (OXPHOS) in sPD fibroblasts uncovers metabolic defects that were otherwise hidden. In this work, we tested the hypothesis that a lead mitochondria-targeted hydroxycinnamic acid derivative would revert the phenotype found in skin fibroblasts from sPD patients. Our results demonstrated that treating human skin fibroblasts from sPD patients with non-toxic concentrations of AntiOxCIN4 restored mitochondrial membrane potential and mitochondrial fission, decreased autophagic flux, and enhanced cellular responses to stress by improving the cellular redox state and decreasing reactive oxygen species (ROS) levels. Besides, fibroblasts from sPD patients treated with AntiOxCIN4 showed increased maximal respiration and metabolic activity, converting sPD fibroblasts physiologically more similar to their sex- and age-matched healthy controls. The positive compound effect was reinforced using a supervised machine learning model, confirming that AntiOxCIN4 treatment converted treated fibroblasts from sPD patients closer to the phenotype of control fibroblasts. Our data points out a possible mechanism of AntiOxCIN4 action contributing to a deeper understanding of how the use of mitochondria-targeted antioxidants based on a polyphenol scaffold can be used as potential drug candidates for delaying PD progression, validating the use of fibroblasts from sPD patients with more active OXPHOS as platforms for mitochondria-based drug development.